Prognostic value of lymph node ratio in surgically treated cases of vulvar cancer: a tertiary care centre experience - Pabashi Poddar; Shilpa Patel; Ruchi Arora; Chetana Parekh; Pariseema Dave; Sangeetha Amin (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveThis study aimed to study the patterns of recurrence in surgically treated cases of vulvar cancer (VC) and determine the factors associated with recurrence, with a special emphasis on lymph node ratio (LNR).MethodsThis retrospective study examined VC patients primarily treated with surgery at our institute from January 2005 to December 2015. Demographic data, clinical characteristics, surgicohistopathological data, adjuvant treatment, follow up, and recurrence site and treatment were studied.ResultsAmong the 111 cases treated, a recurrence rate of 18.9% was noted. Recurrence was most commonly local (61.9%). On univariate and multivariable analyses of clinicopathological parameters, an LNR >20 had the highest hazard ratio for recurrence.ConclusionLNR may provide useful prognostic information in VC patients with positive inguinal lymph node status.